THE EFFECT OF SUPERVISION AND WORK ENVIRONMENT ON EMPLOYEE WORK SPIRIT AT THE DEPARTMENT OF INDUSTRY AND TRADE OF SIBOLGA CITY - Rodia Ipantri; Mhd. Shafwan Koto; Andrian Irsyan (Cattleya Darmaya Fortuna, 2025)
This study aims to determine the effect of supervision and work environment on employee morale at the Department of Industry and Trade of Sibolga City. The type of research used in this study is descriptive and verificative research with a quantitative approach. The sample in this study consisted of employees at the Department of Industry and Trade of Sibolga City, with questionnaires distributed to 30 (thirty) respondents. The results of the study show that based on the coefficient of determination analysis, a value of 0.780 was obtained. This means that 78% of the variation in the dependent variable (employee morale) is explained jointly by the independent variables (supervision and work environment), while the remaining 22% is influenced by other factors not examined in this study, such as communication, leadership, motivation, compensation, incentives, job division, rotation, and others. From the t-test results, it is known that the calculated t-value for supervision is 2.505 > t-table 2.05183 with a significance of 0.019 < 0.05, and for work environment is 6.106 > t-table 2.05183 with a significance of 0.000 < 0.05. Therefore, the hypotheses stating that supervision has a positive and significant effect on employee morale and that the work environment has a positive and significant effect on employee morale at the Department of Industry and Trade of Sibolga City are accepted. Furthermore, from the F-test results, it is known that the calculated F-value is 47.841 > F-table 3.35 and the significance is 0.000 < 0.05. Thus, the hypothesis stating that supervision and work environment simultaneously have a positive and significant effect on employee morale is accepted.